LATE-ONSET CAPSULAR BAG DISTENSION SYNDROME: A REPORT OF TWO CASES - Paraskevas Zafeiropoulos; Andreas Katsanos; Konstantina Gorgoli; Ioannis Asproudis; Miltiadis Aspiotis (Acta Medica, 2014)
Capsular bag distension syndrome is a very rare complication of cataract surgery. Most cases occur after uneventful phacoemulsification with continuous curvilinear capsulorhexis and implantation of an intraocular lens in the capsular bag. The entity presents with reduction of visual acuity and myopic shift in the early-to-late postoperative period. Characteristic findings include the distension of the capsular bag due to the accumulation of milky material and the forward displacement of the intraocular lens. We present two cases with an unusually delayed presentation of 6 and 8 years respectively following phacoemulsification, and describe their successful management with Nd:YAG laser posterior capsulotomy.